Zika Virus Seroprevalence in Urban and Rural Areas of Suriname, 2017 - Langerak, Thomas (J Infect Dis, 2019)
In 2015–2016, a Zika virus (ZIKV) outbreak occurred in the Americas. In 2017, we conducted a ZIKV serosurvey in Suriname in which 770 participants were recruited from 1 urban area and 2 rural villages in the tropical rainforest. All collected samples were tested for presence of ZIKV antibodies using a ZIKV immunoglobulin G enzyme-linked immunosorbent assay and a virus neutralization assay. We found that 35.1% of the participants had neutralizing antibodies against ZIKV. In 1 remote village in the rainforest, 24.5% of the participants had neutralizing antibodies against ZIKV, suggesting that ZIKV was widely spread across Suriname.